2014
DOI: 10.1016/j.eurpsy.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Affective dimensions as a diagnostic tool for bipolar disorder in first psychotic episodes

Abstract: The activation dimension is a diagnostic predictor for bipolar disorder in FEP. The manic dimension contributes to a bipolar diagnosis and its absence can lead to early misdiagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…Thirty-five studies comprising 3180 participants examined the severity of depressive symptoms (Binder et al ., 1998; Zalsman et al ., 2003; Kampman et al ., 2004; Bendall et al ., 2008; Arranz et al ., 2009; Chen et al ., 2009; Strous et al , 2006; Strous et al ., 2009; Barrett et al ., 2010; Cotton et al ., 2010; Roche et al ., 2010; Upthegrove et al ., 2010; Chang et al ., 2011; Pena et al ., 2011; Shoval et al ., 2011; Riedel et al ., 2012; Stowkowy et al ., 2012; Zhao et al ., 2012; Allott et al ., 2013; Tosato et al ., 2013; Arrasate et al ., 2014; Chang et al ., 2014; Stouten et al ., 2014; Chang et al ., 2015; Emsley et al ., 2015; Noto et al ., 2015; Ruggeri et al ., 2015; Sanchez-Gistau et al ., 2015; Ebdrup et al ., 2016; Garcia et al ., 2016; Pawelczyk et al ., 2016; Chang et al ., 2017; Herniman et al ., 2017; Lee et al ., 2017; Zabala et al ., 2017). Three studies reported statistics by sub-group (Binder et al ., 1998; Tosato et al ., 2013; Pawelczyk et al ., 2016), totalling 38 samples.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five studies comprising 3180 participants examined the severity of depressive symptoms (Binder et al ., 1998; Zalsman et al ., 2003; Kampman et al ., 2004; Bendall et al ., 2008; Arranz et al ., 2009; Chen et al ., 2009; Strous et al , 2006; Strous et al ., 2009; Barrett et al ., 2010; Cotton et al ., 2010; Roche et al ., 2010; Upthegrove et al ., 2010; Chang et al ., 2011; Pena et al ., 2011; Shoval et al ., 2011; Riedel et al ., 2012; Stowkowy et al ., 2012; Zhao et al ., 2012; Allott et al ., 2013; Tosato et al ., 2013; Arrasate et al ., 2014; Chang et al ., 2014; Stouten et al ., 2014; Chang et al ., 2015; Emsley et al ., 2015; Noto et al ., 2015; Ruggeri et al ., 2015; Sanchez-Gistau et al ., 2015; Ebdrup et al ., 2016; Garcia et al ., 2016; Pawelczyk et al ., 2016; Chang et al ., 2017; Herniman et al ., 2017; Lee et al ., 2017; Zabala et al ., 2017). Three studies reported statistics by sub-group (Binder et al ., 1998; Tosato et al ., 2013; Pawelczyk et al ., 2016), totalling 38 samples.…”
Section: Resultsmentioning
confidence: 99%
“…Of these patients, 91 (81.25%) and 82 (73.2%) patients were available for analysis at three and five years of follow-up. Sociodemographic and clinical baseline characteristics have been described in a previous publication [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies or sub-samples were excluded when BD I or II were included in the baseline sample and it was not possible to exclude data for these participants (Alloy et al, 2012;Arrasate et al, 2013). Two authors (AR, SC) confirmed decisions about eligibility when there was doubt about the interpretation of inclusion and exclusion criteria.…”
Section: Eligibility Criteriamentioning
confidence: 98%